Reliability, discriminative accuracy, and an exploration of response shift as measured using the satisfaction and Recovery Index over 12 months from musculoskeletal trauma. (February 2021) - Modarresi, Shirin; Walton, David M.
Abstract: Purpose: The Satisfaction and Recovery Index (SRI) is an importance-weighted health-related satisfaction tool intended to be a patient-centric means to capture both the process and state of recovery following musculoskeletal trauma. The purpose of this study was to explore measurement invariance, responsiveness, discriminative accuracy, and potential response shift identifiable within the SRI. Methods: Participants were 111 adults with acute musculoskeletal trauma. Data were collected at baseline, and again at 1, 2, 3, 6, and 12 months post-injury. Other tools used were the Brief Pain Inventory (BPI) and a Global Rating of Change scale. 1-month test-retest reliability (ICC2, 1 ), responsiveness (standardized response mean in stable vs. changed participants), discriminative accuracy (area under the curve for differentiating between recovered and non-recovered), and response shift (change in mean importance scores over the 12-month period) were explored. All but the final analysis were compared against the BPI. Results: Test-retest reliability was excellent across all metrics (ICC2, 1 = 0.83 to 0.88). Responsiveness was greatest for the weighted SRI (SRM = 0.36) with MDC95 of 13.7%. All tools showed significant ability to discriminate between participants nominating recovery vs. non-recovery (AUC≥0.69) though the BPI subscales were significantly better than the SRI. Importance ratings showed small but significant change over time in 7 of the 9 SRI items. Conclusion: This study provides support for the SRI as a useful tool for evaluating recovery, though it seems more valuable for capturing the process rather than state of recovery. While response shift was small, there is enough reason to endorse retention of the importance ratings. Highlights: The Satisfaction & Recovery Index (SRI) is a better evaluation of process than state of recovery from MSK trauma. The SRI is adequately reliable for clinical capture of health satisfaction in a patient-centric way. Importance of SRI items (response shift) showed a small but significant change in most domains over 12 months.